HUBUNGAN KEAKTIFAN DALAM CLUP PROLANIS DENGAN KUALITAS HIDUP LANSIA - Kusumaningrum, Umi Azizah; Nasrudin, Nasrudin (Universitas Pesantren Tinggi Darul Ulum, 2024)
Older people with chronic diseases are currently increasing, especially diabetes mellitus (DM) and hypertension. If this chronic disease is not treated properly, it affects the quality of life of the elderly. Quality of life is a very broad concept that can be influenced by an individual's physical condition, psychology, level of independence, and the individual's relationship with the environment. Prolanis is one of the programs carried out to treat this chronic disease which encourages participants with chronic diseases to achieve optimal quality of life. The aim of this research is to find out the relationship between activeness in the prolanis valve and the quality of life of elderly prolanis participants. The design of this research uses analytical surveys, with a case control approach. The total research sample was 60 respondents. The research results showed that all respondents who were less active in prolanis activities had a poor quality of life (100%), while 68% of respondents who were active in prolanis activities had a high quality of life and 32% a low quality of life. The correlation test using spearman Rho obtained a p-value of 0.004 (<0.05) and a correlation coefficient value of (0.475) which can be concluded that the relationship was positive (directional), which means that the better the respondent's physical activity, the higher the respondent's quality of life. The importance of including activeness in prolanist and obedient activities in carrying out appropriate activities that have been educated while participating in prolanist activities so that the quality of life continues to improve. Keywords: Activity, Prolanis, Quality of Life